2005
DOI: 10.1007/s00534-005-1026-8
|View full text |Cite
|
Sign up to set email alerts
|

Serosal invasion in TNM staging of mass-forming intrahepatic cholangiocarcinoma

Abstract: Serosal invasion showed no survival impact after hepatic resection for mass-forming intrahepatic cholangiocarcinoma. When serosal invasion was omitted from the TNM staging proposed by the Liver Cancer Study Group of Japan, stratification of postoperative survival between stages was more effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 29 publications
5
49
1
4
Order By: Relevance
“…However, this feature has been shown to have no survival impact and that omitting it actually improved the accuracy of staging. 27 Third, no attempt was made to further stratify Nþ patients according to the number of invaded LNs 28 or the LN ratio 29 because of the lack of standardization of LN harvesting. Finally, our strict inclusion criteria (complete clinical and pathological data sets and proven R0 resection) resulted in 69% of our patients being excluded from analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, this feature has been shown to have no survival impact and that omitting it actually improved the accuracy of staging. 27 Third, no attempt was made to further stratify Nþ patients according to the number of invaded LNs 28 or the LN ratio 29 because of the lack of standardization of LN harvesting. Finally, our strict inclusion criteria (complete clinical and pathological data sets and proven R0 resection) resulted in 69% of our patients being excluded from analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The AJCC/UICC staging system is distinct from that for HCC, as the T category considers the tumor number, vascular invasion, visceral peritoneum perforation or extrahepatic direct invasion, and periductal invasion, but not the tumor size. A number of investigators have analyzed the accuracy of both staging systems in predicting patient survival after hepatic resection for ICC, and proposed some modifications based on their findings [14][15][16]47]. Farges et al [16] reported that the current AJCC/UICC staging system was the only system with good accuracy for predicting disease outcome as the other systems failed to do so, including the system proposed by the LCSGJ.…”
Section: Tnm Staging Systems and Prognostic Factorsmentioning
confidence: 99%
“…ICC often spreads via the lymphatic system and postoperative outcomes for patients with lymph node metastases are extremely poor [7][8][9][10][11][12][13][14][15][16][17][18][19][20]; however, to date no consensus among hepatic surgeons has been reached on the indications for surgical treatment of ICC with lymph node metastases and the required extent of lymph node dissection. The extent of both the resection margin and lymph node dissection can be changed by surgeons during hepatic resection for ICC, and it is therefore necessary to clarify their prognostic impact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…first reported that two cases Hepatolithiasis is merger Hepatobiliary cancer (IHHCC), the phenomenon of IHHCC aroused more and more people seriously enough, Hepatolithiasis is a common disease in China and 5% to 10% of hepatolithiasis is known to be associated with cholangiocarcinoma (Uenishi et al, 2005), However, it is difficult to detect early cholangiocarcinoma that occurs as a complication of hepatolithiasis. Clinically, IHHCC remains challenging because it is difficult to diagnose in its early stages, symptoms tend to be vague and insidious in developent, often are diagnosed at an advanced stage.…”
Section: Introductionmentioning
confidence: 99%